Comparative evaluation of different irrigating and irrigant activation system in removal of gutta-percha/sealer during retreatment: An in vitro Micro-CT study - Jyoti Tandon; Rakesh Kumar Yadav; Aseem Prakash Tikku; Vijay Kumar Shakya; Satyendra Kumar Singh (Elsevier, 2022)
Background: The aim of the study was to compare the efficacy of different irrigation and irrigant activation system used as an adjuvant to retreatment rotary files in removal of gutta-percha and sealer from endodontic retreatment using Micro-CT. Method: 64 extracted permanent maxillary central incisor teeth with single canal, were collected and decoronated to standard length of 16 mm. Instrumentation was done using rotary files and obturation was performed using GuttaCore and AH plus sealer. After setting of sealer, initial removal of filling material was performed using ProTaper universal retreatment files (D1, D2, D3). All 64 sample were randomised into four groups (n = 16) Group1: Endodontic syringe irrigation, Group 2: Passive Ultasonic Irrigation (PUI), Group 3: EndoActivator, and Group 4: EndoVac. Micro-CT scanning was performed after obturation, initial removal of filling material by retreatment file and after using experimental protocols of each group, and volume of remaining filling material was calculated using Dolphin software. Statistical analysis performed with one-way ANOVA followed by Tukey's post hoc. Results: A significant reduction in the volume of residual obturation material were found between each group. PUI was superior to the sonic (EndoActivator), negative pressure irrigation technique (EndoVac) and positive pressure irrigation at the coronal, middle third and apical third of the root canal. However, none of the supplementary techniques were able to completely remove the residual obturation material. Conclusion: PUI and EndoActivator were found better in remaining filling material removal, demonstrating clinically useful as supplementary technique in removing remaining obturation material during endodontic retreatment.